Pengaruh Penambahan Ceker Ayam Terhadap Kandungan Gizi Dan Mutu Sensorichiffon Cake - Ani Nuraeni; Wien Kuntari; Faranita Ratih L (Jurnal Gizi dan Kuliner, 2023)
Chiffon cake claw is a chiffon cake product with chicken feet added for its nutritional value, health benefits, and economic value. A study aimed to investigate the impact of adding chicken feet on the nutritional content and sensory quality of chiffon cake. The research involved four stages: preparation, experimentation, laboratory tests, and preference tests. The findings showed that adding claw flour to chiffon cake products increased protein and calcium content by 1081g and 70 mg, respectively. Specuk spices were preferred for taste and scent, while curry spices were preferred for color and texture. The chicken claw chiffon cake is expected to have economic value and competitiveness in the market. Key words: Chiffon cake, chicken claw, nutritional and sensory evaluations